Analysis of the impact of medical and demographic indicators of the Russian population on radiation risk estimates based on the ICRP model - E. A. Kosarlukova; L. V. Repin; A. M. Biblin; R. R. Akhmatdinov (Радиационная гигиена)
The primary quantity used for monitoring exposure levels of the general population and personnel at radiation facilities is the individual effective dose. This metric accounts for variations in the radiosensitivity of specific organs and tissues by employing corresponding tissue weighting factors recommended by the ICRP. These factors were derived based on medico-demographic data from two artificially constructed populations: "Euro-American" and "Asian." Estimates of relative harm, calculated from risk assessments, served as the basis for establishing the recommended values of tissue weighting factors for organs and tissues. However, the use of effective dose as a risk measure in cases of non-uniform exposure within specific populations raises questions about the appropriateness of applying alternative tissue weighting factors in its calculation to more rigorously account for differences in relative radiosensitivity. The study aims to assess whether the recommended values of nominal risk coefficients and weighting factors for organs and tissues provide a comparable level of safety for the Russian population compared to that provided for the ICRP nominal population. Materials and Methods: The assessment of radiation-induced cancer risk was conducted using Russian medico-demographic data from 1993 to 2022, applying the interpopulation radiation risk transfer model from ICRP Publication 152. Results and Discussion: The calculations indicate that risk estimates for most organs and tissues in the Russian population have gradually increased for males over the 30- year period. However, with the exception of thyroid cancer risk in females, these estimates do not exceed the corresponding values used to establish the tissue weighting factors. Conclusion: The current system of risk indicators and dose limits provides an adequate level of protection for the Russian population and does not require revision until international approaches to radiation protection are updated.